(untitled) (Revista Venezolana de Salud Pública, 2020)
The presence and proliferation of fungi in the hospital environment can represent a risk factor for the health of patients and their families, since they can cause nosocomial infections. The objective of this study was to identify the different filamentous fungi present in the areas: adult emergency, pediatric emergency, Intensive Care Unit and operating room of the “Antonio Patricio de Alcalá” University Hospital in the city of Cumaná, Sucre state in Venezuela. The study was descriptive, cross-sectional and non-experimental. The count of the colony-forming units per plate of the filamentous fungi was performed in Petri dishes with potato dextrose agar, exposed in the spaces mentioned. Subsequently, the fungal colonies present were isolated and identified. Significant differences were observed in the counts obtained from the different studied sites (p <0.05), adult and pediatric emergency presented the highest counts, followed by the Intensive Care Unit and the Operating Room. No significant differences were observed between the sampling months (p> 0.05). The fungal genera that were isolated in the highest proportion were: Aspergillus (36.3%), Penicillium (28.2%), Fusarium (12.7%) and Cladosporium (9.1%). The most frequently isolated species were: A. niger (14.2%), P. citrinum (12.7%), F. poae (12.7%) and C. herbarum (9.1%). The results obtained showed that several of the fungi identified in the present study should be considered as potential pathogens for patients and other people in the hospital.